Pengaruh Rasio Keuangan terhadap Kinerja Bank Umum Syariah (BUS) Periode 2019-2021 - Selamat Muliadi (Global Financial Accounting Journal, 2022)
Purpose – This research purposes to know the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Return on Assets (ROA) in Islamic Commercial Banks (BUS) for the period 2019-2021. Research Method – Research method is applicated the quantitative descriptive method and the sample is Islamic Commercial Banks (BUS) and which are consistently publish quarterly financial report period 2019-2021. The sample is collected by using purposive method, and multiple linear regression for analyzing the data. Findings – This study found that CAR and NPF has significant effect on ROA in the Islamic Banking while FDR does not have a significant effect on ROA. In general, three independent variables influence ROA about 67,2%. Implication – This study assists to understand the bank management specifically in financial performance. In other hand, the findings can be preferences in making policy for government, helpful to use additional references about comparison of Islamic Banks Financial performance and its influence.